Dominica : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
The Dominican government's main policy objective is to create the basis for the sustained growth of output and employment through economic diversification and financial stability. The structure of the economy has continued to shift away from banana production, with services gaining importance as a key source of growth. In addition to streamlining the public investment program, the early adoption of fiscal measures will maintain soundness in the public finances. A more determined pursuit of the structural reform agenda will help increase economic efficiency.